The Decisions Taken by the Brazilian Maritime Court in the Judiciary: The Contradictory Value Attributed to the Technical Opinions Provided by the Administrative Body in the Brazilian Legal Order Scope - Larissa Thomaz Coelho (Revista de Política Judiciária, Gestão e Administração da Justiça, 2016)
This article aims to analyze the administrative decisions issued by the Maritime Court when placed under the judicial branch. Through a critical reflection, it seeks to understand the nature of the decisions resulting from this body, which belongs to the executive branch, into the Brazilian legal system, in order to understand the relationship between them and the decisionsoftheordinarycourts.Italsoseekstoexaminethephenomenonofjudicialization in this area as well as the diverse valuation that the law and the judiciary branch apply to the technical reports issued by the Maritime Court. O presente artigo apresenta como objetivo analisar as decisões administrativas emanadas pelo Tribunal Marítimo quando colocadas no âmbito do Poder Judiciário. Por meio de uma reflexão crítica, visa entender a natureza das decisões advindas desse órgão, que pertence ao Poder Executivo, no ordenamento jurídico brasileiro, de modo a compreender a relação existente entre elas e as decisões dos tribunais comuns. Busca examinar o fenômeno da judicializaçãopresentenesseâmbito,bemcomoavaloraçãodiversadispensadapelaleie pelo judiciário aos pareceres técnicos elaborados pelo Tribunal Marítimo.